Potential of anti-tumorigenicity and anti-metastasis of annona muricata (soursop leaves) on mcf-7 and mda-mb231 breast cancer cells line - Ab Rahman , Husna Shakirah (2017)
Breast cancer is the leading cancer in Malaysia and among women. Annona Muricata or Graviola leaves or Soursop leaves also known as ‘the cancer killer’ has been used worldwide as a complementary for treatment of cancer. Many studies have shown that Annona Muricata has a potential of antitumorigenicity and chemoprevention to treat cancer. Hence, in this study, we are trying to proof the cytotoxic effect and metastatic effect of Annona Muricata on breast cancer cell lines.This study aims to determine the cytotoxic effect of the extract of the soursop (Annona Muricata) leaves, the apoptotic effect and effect on cell cycle after treatment of the extracts on the MDA-MB 231 and MCF-7 breast cancer cell lines.Extracts from Annona Muricata was prepared using soxhlet method using different solvents (hexane, Ethyl acetate, methanol and water). MDA-MB 231 (ER/PR negative) and MCF-7 (ER/PR positive) breast cancer cell line used in the study. The cytotoxic effect was analysed by counting the number of cells inhibition and identified the IC50 (the percentage of cell populations inhibited by 50% after treatments) of each extracts, the cell proliferation was observed under microscope. The apoptotic effect of MDA-MB 231 and MCF-7 breast cancer cell line was done by using Annexin V-Fitc Apoptosis Dtec Kit (6140592[1] (31.10.2017). While, the effect of cell cycle of MDA-MB 231 and MCF-7 breast cancer cell line was done by using Cycletest plus DNA Reagent Kit (6193798[1 (31.07.2017). Both tests are then analysed using flow cytometer.From the experiment, ETAC was the best extract for observing cytotoxic effect for MDA-MB 231 cells line and hexane was the best extract for MCF-7 cells line. There was a decreased of the number of cells populations for both MDA-MB 231 and MCF-7 cells line after treatment with Annona Muricata in different concentrations and time. ETAC and hexane gave best apoptotic effect at late phase of apoptosis, while Tamoxifen gave best apoptosis effect during early phase. Besides, there was significant G1 phase arrest of MDA-MB 231 and MCF-7 cells line after treatment with ETAC and hexane, respectively, as well as Tamoxifen. There was suppression for migration for MDA-MB 231 and MCF-7 cells lines after treatment with ETAC and hexane.Annona Muricata has a potential of anti-tumorigenicity on MCF- 7 and MDA-MB 231 breast cancer cell lines. It gives changes in morphology of the breast cancer cell, as well as cytotoxic and apoptotic effect. Moreover, Annona Muricata also induces G1 cell cycle arrest in breast cancer cell lines. In addition, soursop leaves can help inhibit breast cancer migration that suggested of metastatic prevention. Thus, Annona Muricata can be recommended for use as complement in xv breast cancer patient and as prevention for tumour occurrence. Even though the potential anti-tumorigenicity of Annona Muricata can be observed in this study, Tamoxifen still gave better result compared to Annona Muricata in term of cell inhibition and metastatic effect.